2015
DOI: 10.1021/acs.joc.5b00283
|View full text |Cite
|
Sign up to set email alerts
|

4-Fluoro and 4-Hydroxy Pyrrolidine-thioxotetrahydropyrimidinones: Organocatalysts for Green Asymmetric Transformations in Brine

Abstract: The synthesis of both trans- and cis-diastereomers of pyrrolidinine-thioxotetrahydropyrimidinone bearing either a fluorine or a hydroxyl group was accomplished. The new compounds were tested for their catalytic properties in a variety of asymmetric organic transformations and compared with the first generation catalyst. It was found that the new catalysts could efficiently catalyze the reactions in brine, without the use of organic solvent, and by employing an almost stoichiometric amount of reagents. Thus, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 53 publications
2
22
0
Order By: Relevance
“…Kokotos et al. applied novel 4‐fluoropyrrolidine–thioxotetrahydropyrimidinone catalyst C98 to this reaction, which was conducted in brine . The best results were achieved with respect to reaction yield and diastereoselectivity.…”
Section: Water As a Medium For Organocatalytic Reactionsmentioning
confidence: 99%
“…Kokotos et al. applied novel 4‐fluoropyrrolidine–thioxotetrahydropyrimidinone catalyst C98 to this reaction, which was conducted in brine . The best results were achieved with respect to reaction yield and diastereoselectivity.…”
Section: Water As a Medium For Organocatalytic Reactionsmentioning
confidence: 99%
“…They observed that 1,4-cyclohexadienone with catalyst 16 with phenylnitrodiene gave the corresponding bicyclic compound in 48% yield, excellent diastereoselectivity (dr > 99:1) and a 97% ee [40]. …”
Section: Chiral Organocatalysis For the Synthesis Of Bicyclo[321mentioning
confidence: 99%
“…Not only aromatic nitroalkenes with electron-withdrawing and electron-donating substituents were suitable electrophiles, but also some aliphatic nitroalkenes and aromatic nitrodienes were successfully used as Michael acceptors. The use of brine and the possibility of reducing the reagent ratio to almost stoichiometric values by using catalyst 52 made this protocol green and effective [ 80 ].…”
Section: Carbon Nucleophilesmentioning
confidence: 99%